2020
DOI: 10.15408/jkv.v6i1.14837
|View full text |Cite
|
Sign up to set email alerts
|

The Starting Material Concentration Dependence of Ag3PO4 Synthesis for Rhodamine B Photodegradation under Visible Light Irradiation

Abstract: Synthesis of Ag3PO4 photocatalyst under the varied concentrations of AgNO3 and Na2HPO4·12H2O as starting material has been successfully synthesized using the co-precipitation method. The concentration of AgNO3 is 0.1; 0.5; 1.0; and 2.0 M, whereas Na2HPO4·12H2O is 0.03; 0.17; 0.33; and 0.67 M, respectively. The co-precipitations were carried out under aqueous solution. As-synthesized photocatalysts were examined to degrade Rhodamine B (RhB) under blue light irradiation. The results showed that varying concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The results show a = b = c ∼ 5.989 Å and D XRD ∼ 44 nm for the Ag/P 3:1 sample, which are relatively consistent with previous studies. [4,9,12] decreases. This leads to a slight decrease in lattice parameters, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The results show a = b = c ∼ 5.989 Å and D XRD ∼ 44 nm for the Ag/P 3:1 sample, which are relatively consistent with previous studies. [4,9,12] decreases. This leads to a slight decrease in lattice parameters, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 95%
“…[1,2] As the formation of electron/hole pairs on the surface of APO particles plays an important role in the photocatalytic performance, many studies have been carried out with the aim to control the particle size or particle morphology to increase the specific surface area. [3][4][5][6] The studies showed that synthesis parameters such as the precipitating agents, [7,8] the ratios of the starting materials, [9,10] the concentration of the reaction catalysts, [5,11] the fabrication time, [3,4,12] and pH conditions [13] greatly influence the size and morphology of the particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations